Oh no, gotta go! - Elya, Susan Middleton, 1955- (G.P. Putnam's Sons, 2003)
While out for a Sunday drive with her parents, a little girl suddenly remembers what she forgot to do before she left her home. Text includes some Spanish words and phrases.